2019
DOI: 10.1021/acs.jafc.9b03699
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Cerbinal and Its Analogues Cyclopenta[c]pyridines: Synthesis and Discovery as Novel Pest Control Agents

Abstract: Owing to the changing needs of agriculture, the exploration of new pest control agents remains as critical as ever. The analogues 3a–3v of the natural product cerbinal were synthesized from genipin by an efficient and practical method under additive-free conditions. The antiviral and insecticidal effects of cerbinal and these cyclopenta­[c]­pyridines (3a–3v) were evaluated systematically. Most of the synthesized compounds exhibited higher anti-TMV activities than the lead compound cerbinal. Compound 3s (2-(4-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…13 Several research groups have developed lead compounds with activity against plant viruses. For example, Song et al designed and synthesized the α-amino phosphonate dufulin, which is an efficient antiviral agent; 14,15 Hao et al found that many alkaloids, including lycorine and eudesmanolides, exhibited activities against plant viruses; 16, 17 Wang et al isolated a series of marine natural products as anti-plant virus lead compounds; 18−21 and Xia 22 and Li 23 et al reported that genipin, cerbinal, and their derivatives exhibit antiviral activities.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…13 Several research groups have developed lead compounds with activity against plant viruses. For example, Song et al designed and synthesized the α-amino phosphonate dufulin, which is an efficient antiviral agent; 14,15 Hao et al found that many alkaloids, including lycorine and eudesmanolides, exhibited activities against plant viruses; 16, 17 Wang et al isolated a series of marine natural products as anti-plant virus lead compounds; 18−21 and Xia 22 and Li 23 et al reported that genipin, cerbinal, and their derivatives exhibit antiviral activities.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Several research groups have developed lead compounds with activity against plant viruses. For example, Song et al designed and synthesized the α-amino phosphonate dufulin, which is an efficient antiviral agent; , Hao et al found that many alkaloids, including lycorine and eudesmanolides, exhibited activities against plant viruses; , Wang et al isolated a series of marine natural products as anti-plant virus lead compounds; and Xia and Li et al reported that genipin, cerbinal, and their derivatives exhibit antiviral activities. Although there has been considerable progress in the study of how plants develop resistance to viruses, there are only a few satisfactory plant virus inhibitors and even fewer therapeutic agents, such as ningnanmycin, ribavirin, and moroxydine hydrochloride cupric acetate, and most of the reported control rates in field tests are below 60% (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al found series of marine natural products could be used as anti-plant-virus lead compounds [11][12][13][14] . Xia et al [15] found genipin and their derivatives and Li et al [16] found cerbinal and their derivatives both exhibited anti-virus activity. Although considerable progress in developing resistance to plant viruses has been made, few satisfactory plant-virus inhibitors and even fewer therapeutic agents have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have made important progress in research on anti-plant-virus agents. For example, Song et al developed the α-amino phosphonate antiviral agent dufulin; , Hao et al found that eudesmanolides, matrine-type alkaloids, and lycorine exhibit anti-plant-virus activities; Li et al reported that hemigossypol, cerbinal, and some of their derivatives are active against plant viruses; , and Wang et al discovered a series of marine natural products as anti-plant-virus lead compounds. …”
Section: Introductionmentioning
confidence: 99%